Kemampuan berpikir aljabar mahasiswa calon guru matematika materi pecahan aljabar - Putri, Finola Marta; Herlina, Sari (SIGMA DIDAKTIKA: Jurnal Pendidikan Matematika, 2024)
This research aims to analyze and describe the achievement of learning indicators for algebraic fraction material for prospective mathematics teacher students. The research method is descriptive qualitative. This research was conducted on 36 student teacher candidates for class 3C in the odd semester of 2022 at a university in Banten province. The instruments used were 2 test questions on the description of algebraic fractions with 1 question on one-variable linear inequalities material adopted from the Basic Mathematics book and 1 question on algebra form material adopted from the Mathematics Book of the Ministry of Education and Culture, Independent Curriculum for Class VII, as well as documentation. The data analysis technique presents data and concludes. This research concludes that the achievement of learning indicators for algebraic fraction material for prospective mathematics teacher students is relatively low, with 8% of mathematical understanding ability in the high category, 70% in the medium category, and 22% in the low category. The dominant error in one-variable linear inequality material is omitting the variable in the denominator, and the dominant error in algebraic form material is that the position of the numerator variable in the denominator of the problem is not changed when the coefficient and operating sign have changed.